Technopreneurship in Pro-Environmental Behavior for Sustainable Carbon Emission Reduction in Central Kalimantan - Andhella, Sylviana; Djajadikerta, Hamfri; Marjuka, Martinus Yuwana (Pandawan, 2024)
This study examines the integration of technopreneurship with pro-environmental behavior to achieve sustainable carbon emission reduction in Central Kalimantan. Focusing on the Dayak-Banjar communities, the research aims to develop a model that leverages local wisdom and technopreneurial activities to promote environmental conservation. The methodology includes qualitative research through interviews and questionnaires distributed in Baung, Muara Dua, and Kuala Pembuang villages. Findings reveal that local communities, deeply affected by environmental degradation, are willing to adopt pro-environmental behaviors. Key factors influencing this change include attitudes, subjective norms, perceived behavioral control, and knowledge. The study highlights the potential of technopreneurship in promoting sustainable practices and provides a foundation for designing policies that support pro-environmental behavior through technopreneurship. By fostering pro-environmental behavior within local communities, this research demonstrates that it is possible to balance ecological conservation with economic growth, aligning with SDG 13, SDG 15, and SDG 8.